Synthesis of Calcium Carbonate Polymorphs in the Presence of Methionine - Yin, De-Xin; Cao, Jian; Cui, Shu-Sen; Li, Li-Sen (Asian Journal of Chemistry, 2014)
Osteogenesis relates to biomineralization of CaCO3 deposition doped with multiple amino acids. The crystallization of CaCO3 in the presence of methionine with extremely unusual, ginger-shaped morphology is reported in this article. We show that unusual ginger-shaped CaCO3 vaterite crystals selectively grow from the edge of rhombohedral calcite crystals with certain degree of preferred orientation. The unusual morphology and the growth process of the ginger-shaped vaterite CaCO3 crystals were discussed with emphasis on methionine mediated selective binding and oriented aggregation/attachment of vaterite nanocrystals. Moreover, crystallization of CaCO3 in the presence of methionine, a classified nonpolar amino acid, revealed atypical polymorphic selectivity, where vaterite is the major component. With all these in regards, this study further confirmed that nature of amino acid is crucial in achieving the desired selectivity in polymorph nucleation, as well controlling the crystalline nature and morphology of the CaCO3 crystals.